A Fault Diagnosis Method for Urban Rail Signal System Based on Statistical Model - TAN Litian; CHEN Xin; LI Pengdong (Kongzhi Yu Xinxi Jishu)
In order to realize fast and accurate fault location of urban rail CBTC signal system, a fault diagnosis method based on statistical model was proposed in this paper. The data of ZC subsystem before and after fault for a certain period of time is used, the probability distribution curve is fitted with the training data of Katz backoff method, and a statistical binary Markov model is established.In commissioning and operation stage of Changsha Subway Line 4, through statistical sampling test data verification, the results show that the method can provide an effective judgment basis for rapid fault location and realize fault classification of ZC subsystem quickly and effectively.